Treatment of dairy wastewater using enzyme pre-treatment coupled with an expanded granular sludge bed reactor - Moodley, Hugendra (Department of Civil Engineering, 2025)
Dairy consumption is rising due to the rapid growth of the population, necessitating increased dairy production to meet this demand. Consequently, the wastewater produced by dairy plants is also increasing significantly. The dairy industry, already one of the biggest contributors to pollution, generates large volumes of wastewater contaminated with toxic substances. These substances adversely affect the water sources into which the wastewater is released, whether fully or partially. Contaminants such as high concentrations of fats, oils, and greases (FOGs), nitrogen, phosphate, chemical and biological oxygen demand (COD and BOD) are found in the wastewater. This study investigates the treatment of dairy wastewater (DWW) using a biological pretreatment coupled with an anaerobic down-flow expanded granular sludge bed reactor (DEGBR). The DEGBR system, previously utilized in the treatment of PSW, showed satisfactory removal efficiencies with the use of a bioremediation agent, Eco-Flush. However, Eco-Flush was found to contribute to the increase in dissolved oxygen (DO) levels due to aeration, leading to the identification and use of a new enzyme named Momar in this study. The pre-treatment stage aimed to determine the optimum dosage of Momar, focusing on the removal of FOGs to mitigate clogging in the DEGBR. The results of the pre-treatment stage were satisfactory, with a 42% reduction in DO, and removal efficiencies of 16% for COD, 20% for Total Suspended Solids (TSS), and 70% for FOG. The pre-treatment stage successfully removed a significant amount of FOGs from the wastewater. The DEGBR was operated with three different hydraulic retention times (HRTs), and the removal efficiencies of COD, TSS, and FOG were compared. At 36 hours, the removal efficiencies were 38% for COD, 55% for TSS and 76% for FOG; at 24 hours, they stood at 36%, 48% and 68%, and at 12 hours, the values were 48%, 43% and 74%. The overall average removal efficiencies of the DEGBR for COD, TSS, and FOG were 39%, 49%, and 73%, respectively. Overall, the combined system produced satisfactory results with removal efficiencies of COD, TSS, and FOG, which are 48%, 56%, and 71%, respectively. In conclusion, the biological system coupled with a biological pre-treatment effectively treated high-fat wastewater. It is recommended that a thorough analysis be conducted on Momar to identify the impact of the enzymes on wastewater. In the future, the system should be operated again with dairy wastewater for a longer period, addressing system issues, and incorporating regular backwashing to prevent clogging.